TRANSFORMATIVE LEARNING THROUGH PROJECT-BASED LEARNING: ENHANCING STUDENT ENGAGEMENT AND CREATIVITY IN WRITING - Syamsuddin, Syamsuddin; Tahir, Muh.; Idris, Idris; Efendi, Efendi; Asrianti, Asrianti; Gazali, Gazali (JURNAL EDUSCIENCE, 2025)
Purpose—This research aims to explore the transformative impact of Project-Based Learning (PjBL) in improving engagement and creativity in short stories. It also discusses the limitations of the traditional method, which makes the teacher the center of the study and limits students' active participation and creative exploration.Methodology—Descriptive qualitative research was used, involving 17 students. This research was conducted in two weeks and implemented PjBL in three phases: preparation, implementation, and evaluation. Data collection methods included classroom observation, semi-structured interviews, and analysis of students' creative output. The collected data were analyzed based on engagement indicators, creativity dimensions, and narrative quality.Findings - The research revealed a significant increase in student engagement; 82% of students actively engaged in group discussion, and 88% responded to the teacher's instruction. The average creativity score was 3,55 out of 4, which was categorized as "Very High," specifically in originality and imaginative language use. The quality of the short story was scored "High," showing the strength in the originality of the theme and creativity of diction. Students highlight the PjBL characteristics of autonomy and collaboration as the main factors in enriching their learning experiences. This finding offers valuable knowledge for the teacher, curriculum designer, and policy maker to integrate an innovative student-centered pedagogical approach in writing instruction.Contribution—The combination of PjBL would enable the school to foster creativity, engagement, and problem-solving skills, equipping the students with the important competencies for the demands of 21st-century education.